2006
DOI: 10.1002/ijc.21948
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induces the fragile histidine triad methylation in human esophageal squamous epithelial cells

Abstract: The fragile histidine triad (FHIT) gene has been proposed to have an important role in very early carcinogenesis. Methylation of the FHIT gene is associated with transcriptional inactivation in esophageal squamous cell carcinoma, and FHIT inactivation has been linked to smoking-related carcinogenesis. In this study, we confirmed methylation of the FHIT gene in human esophageal squamous epithelial cells (HEECs) and examined whether nicotine induced alteration of FHIT. Methylation status in the promoter region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
2
34
0
3
Order By: Relevance
“…Morimoto et al (15) and Shrubsole et al (16) (30) and that tobacco smoking is associated with hypermethylation of TSG in nonsmall cell lung cancer (31). Chan et al (32) We found ten studies (1,5,7,10,12,13,16,29,33,34) regarding the association between ethanol consumption and colon polyps where all polyps were diagnosed by full colonoscopy.…”
Section: T a B L E 3 Ad J U S T E D Od D S Ra T I O S F O R Co L O mentioning
confidence: 88%
“…Morimoto et al (15) and Shrubsole et al (16) (30) and that tobacco smoking is associated with hypermethylation of TSG in nonsmall cell lung cancer (31). Chan et al (32) We found ten studies (1,5,7,10,12,13,16,29,33,34) regarding the association between ethanol consumption and colon polyps where all polyps were diagnosed by full colonoscopy.…”
Section: T a B L E 3 Ad J U S T E D Od D S Ra T I O S F O R Co L O mentioning
confidence: 88%
“…Tobacco contains more than 60 carcinogens (Hoffmann et al, 1990;Hecht et al, 2006) and tobacco exposure is known to induce genetic and epigenetic changes in esophageal squamous and lung cancer cells (Hecht et al, 1999;Soma et al, 2006;Liu et al, 2007;Lin et al, 2010;Huang et al, 2011). NNK is a key ingredient of tobacco smoke carcinogens.…”
Section: -(Methylnitrosamino)-1-(3-pyridyl)-1-butanone Induces Retinmentioning
confidence: 99%
“…This may result in changes in the genetic "program" that controls lung development, maintenance of lung structure and aging of lung tissue, which may render the lungs more prone to disease. Since nicotine is associated with DNA methylation [35], it is possible that it may change the program that is maintaining homeostasis in the developing lung in the long term and in this way contribute to the adult onset of diseases. In addition, a product of nicotine metabolism is nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) which induces DNA damage which is associated with an increase in mutational events [36].…”
Section: Nicotine Uptake and Metabolism During Pregnancymentioning
confidence: 99%